Impact of Cognitive VR vs. Traditional Training on Emotional Self-Efficacy and Cognitive Function in Patients with Multiple Sclerosis: A Retrospective Study Focusing on Gender Differences - Maria Grazia Maggio; Alessandra Benenati; Federica Impellizzeri; Amelia Rizzo; Martina Barbera; Antonino Cannavò; Vera Gregoli; Giovanni Morone; Francesco Chirico; Angelo Quartarone; Rocco Salvatore Calabrò (Brain Sciences)
Background and aim: While conventional MS rehabilitation primarily addresses physical and cognitive symptoms, recent advances in VR technology offer immersive environments that facilitate both emotional and cognitive skill development. The purpose of this study is to evaluate the impact of VR-based training on emotional self-efficacy in multiple sclerosis (MS) patients and examine its association with cognitive function improvement. Additionally, this study aims to explore potential gender differences in these outcomes, hypothesizing that gender may influence the effectiveness of VR-based rehabilitation, which could inform more tailored approaches for emotional and cognitive rehabilitation in MS. Method: The present retrospective study analyzed data from 43 MS patients undergoing cognitive and behavioral rehabilitation at the IRCCS Centro Neurolesi “Bonino Pulejo” in Italy, comparing a VR intervention group (VR-G) and a control group receiving traditional rehabilitation. Emotional self-efficacy, depression, and anxiety were assessed, alongside cognitive function pre- and post-intervention. Results: Findings indicate that the VR-G showed significant improvements in managing negative emotions, reduced depressive and anxiety symptoms, and enhanced cognitive performance, particularly in verbal learning and working memory. Gender-based analysis revealed a trend suggesting that females in the VR-G may exhibit greater improvements in positive emotional self-efficacy, although this difference did not reach statistical significance. Spearman’s correlation highlighted associations between emotional self-efficacy and cognitive gains, supporting the potential of VR to foster both emotional and cognitive resilience. Conclusions: These findings suggest that VR training may provide a tailored approach for MS rehabilitation, enhancing therapeutic outcomes by integrating emotional and cognitive training in an immersive setting. Further research should investigate long-term effects and neurophysiological correlates of VR training to optimize MS rehabilitation.